2020
DOI: 10.1590/s1677-5538.ibju.2019.0526.1
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Comment: The impact of perioperative complications on favorable outcomes after artificial urinary sphincter implantation for post-prostatectomy incontinence

Abstract: The Artificial Urinary Sphincter (AUS) is considered the gold standard treatment of non-neurogenic male urinary incontinence in several Guidelines (1-3). Despite the high rates of initial continence, a significant number of patients will need some type of revision, generally due to infection, urethral erosion, return of incontinence or mechanical problems (4). Failure rates and the need for revision are generally associated with patient characteristics and history of previous treatment-for the cancer or for ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A retrospective cohort study published in 2020 that analyzed data of 105 patients who underwent primary implantation for non-neurogenic stress urinary incontinence reported that UTI occurred in 7.6% of patients. Furthermore, they reported that UTI was an indepen-dent risk factor for device explantation [25]. This highlights the importance of prevention, recognition, and treatment of post-operative urinary tract infection.…”
Section: Urinary Tract Infectionmentioning
confidence: 98%
See 1 more Smart Citation
“…A retrospective cohort study published in 2020 that analyzed data of 105 patients who underwent primary implantation for non-neurogenic stress urinary incontinence reported that UTI occurred in 7.6% of patients. Furthermore, they reported that UTI was an indepen-dent risk factor for device explantation [25]. This highlights the importance of prevention, recognition, and treatment of post-operative urinary tract infection.…”
Section: Urinary Tract Infectionmentioning
confidence: 98%
“…Urinary tract infection (UTI), hematuria, and urinary retention have all been reported as perioperative complications of AUS implantation [16,[24][25][26]. Violation of the urethra or instrumentation of the urethra with either a catheter or cystoscope place the patient at risk.…”
Section: Urinary Tract Infectionmentioning
confidence: 99%